Group A streptococcal primary peritonitis in an otherwise healthy adolescent female - Torbjorg Holtestaul, M.D; Allison Langs-Barlow, M.D; Meade Barlow, M.D (Elsevier, 2021)
Group A streptococcal (GAS) primary peritonitis is a rare clinical entity, particularly in the pediatric population. Traditionally patients with primary peritonitis, particularly those with underlying medical conditions such as nephrotic syndrome and liver disease, are managed non-operatively with antibiotics. However, most patients presenting with GAS primary peritonitis undergo operative intervention as it is difficult to exclude an intra-abdominal source in an otherwise healthy child with clinical evidence of peritonitis. We present a case of a 16-year-old female with GAS primary peritonitis following a previous hospitalization for GAS pyelonephritis. We additionally review the recent pediatric literature on GAS primary peritonitis and discuss options for diagnosis and management.